Analisis Perbandingan Pengalaman Pengguna pada Aplikasi Halodoc dan Alodokter menggunakan User Experience Questionnaire (UEQ) - Nixon Okabashi Hendrawan; Eriq Muhammad Adams Jonemaro; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Covid-19 pandemic affecting all of our life's aspects, health included. Until the founding of technology development called Telemedicine. Telemedicine is online healthcare that helps the user to get medicated or have a health consultation without having to come to the medical center or hospital. There's several online consultation media available nowadays, for example Halodoc and Alodokter. User experience evaluation is being conducted towards Halodoc and Alodokter because both have similarities in its main features. Evaluation being done using User Experience Questionnaire (UEQ) in the form of Google Form for an easier distribution. 20 participants' data collected, and acquired that Halodoc got a positive evaluation and Alodokter got a quite positive evaluation. Although being compared, Halodoc generally got a better result than Alodokter. Both have similarities which are that their highest value is in their Efficiency scale and pragmatic quality's aspect got the lowest value. Therefore can be concluded that the aspect which needs an improvement is the pragmatic quality's aspect so the user can be more engaged and more impressed on using the application.